False positive fourth generation HIV test in a patient with severe malaria. (June 2019) - Stempel, Jessica M.; Mora Carpio, Andres L.; Puga, Daniel; Perloff, Sarah
Highlights: Infections and malignancies can lead to false positive 4th generation assays. We report the first case of malaria causing a false positive 4th generation HIV test. The CDC algorithm is essential for clinicians when approaching discordant results. Potential antigen cross-reactivity is possible with ARCHITECT HIV Ag/Ab combo assay. Abstract: Severe malaria is an uncommon diagnosis in the United States. However, awareness of signs, symptoms, and treatment options is imperative in order to promptly initiate optimal therapy. False positive human immunodeficiency virus (HIV) results are rare in the setting of acute malaria infection and with the introduction of newer fourth-generation immunoassays. The Centers for Disease Control algorithms assist in confirming true HIV infection (Branson et al. 2014).